2015
DOI: 10.1021/acs.analchem.5b01449
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Transmembrane Protein Mobility in Polymer-Supported Lipid Bilayers Derived from Cell Membranes

Abstract: Supported lipid bilayers (SLBs) have contributed invaluable information about the physiochemical properties of cell membranes, but their compositional simplicity often limits the level of knowledge that can be gained about the structure and function of transmembrane proteins in their native environment. Herein, we demonstrate a generic protocol for producing polymer-supported lipid bilayers on glass surfaces that contain essentially all naturally occurring cell-membrane components of a cell line while still re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 51 publications
8
115
0
Order By: Relevance
“…There has also been progress in using composite membranes made from cell-derived membrane components mixed with PEGylated liposomes to engender the SLB with both biologically relevant material (receptors, etc.) and a built-in cushion to maintain constituent mobility [51,52]. Other work has demonstrated the ability to form bilayers from cell plasma membrane blebs as a way to incorporate transmembrane proteinaceous receptors and complete native cell materials into planar geometries [13,53,54].…”
Section: Biomimetic Platformsmentioning
confidence: 99%
“…There has also been progress in using composite membranes made from cell-derived membrane components mixed with PEGylated liposomes to engender the SLB with both biologically relevant material (receptors, etc.) and a built-in cushion to maintain constituent mobility [51,52]. Other work has demonstrated the ability to form bilayers from cell plasma membrane blebs as a way to incorporate transmembrane proteinaceous receptors and complete native cell materials into planar geometries [13,53,54].…”
Section: Biomimetic Platformsmentioning
confidence: 99%
“…The advent of two‐dimensional membrane protein affinity capturing in a lipid‐bilayer environment may potentially be expanded from local capturing and enrichment of a single type of membrane protein to isolation of specific membrane proteins in a complex matrix, once the concept is extended to supported membranes derived directly from live cells. Parallel activities to address the challenge of converting cell‐membrane material into a continuous SLBs are indeed ongoing . If such efforts are successfully combined with the concept presented herein, we believe that the approach may provide several new exciting opportunities for membrane protein analysis, such as identification of unknown membrane protein–protein or lipid–protein interactions as well as drug screening of membrane‐embedded receptors including kinetic profiling facilitated by the microfluidic setup.…”
Section: Figurementioning
confidence: 95%
“…Parallel activities to address the challenge of converting cell-membrane materiali nto ac ontinuous SLBs are indeed ongoing. [31] If such efforts are successfully combined with the concept presented herein, we believe that the approachm ay provide several new exciting opportunities for membrane protein analysis, such as identification of unknown membrane protein-protein or lipid-protein interactions as well as drug screening of membrane-embedded receptors including kinetic profiling facilitated by the microfluidic setup.…”
mentioning
confidence: 97%
“…Although various polymer supports, such as chemically immobilized (or cross-linked) gels (Kühner et al, 1994;Kuhl et al, 1998), polymer brushes (Rehfeldt et al, 2006;Kaufmann et al, 2011), and polyelectrolyte multilayers (Wong et al, 1999;Delajon et al, 2005), have been reported, not all hydrophilic polymer films could act as good supports for membranes. Since it is even possible to spread "native cell membranes" uniformly on polymer cushions or spread cell membrane extracts mixed with lipopolymercontaining vesicles (Pace et al, 2015), such systems can be considered as a "1/2 model" of cell-cell contact (Figure 3A). One of the most important criterion in choosing the polymer material is that the polymer-supported membranes must be thermodynamically stable.…”
Section: Polymer-supported Membranes As the Model Of Biointerfacesmentioning
confidence: 99%